Adverse drug events leading to emergency department visits: A multicenter observational study in Korea. - Min-Gyu Kang; Ju-Yeun Lee; Sung-Il Woo; Kyung-Sook Kim; Jae-Woo Jung; Tae Ho Lim; Ho Joo Yoon; Chan Woong Kim; Hye-Ran Yoon; Hye-Kyung Park; Sang-Heon Kim (PLoS ONE, 2022)
Adverse drug events are significant causes of emergency department visits. Systematic evaluation of adverse drug events leading to emergency department visits by age is lacking. This multicenter retrospective observational study evaluated the prevalence and features of adverse drug event-related emergency department visits across ages. We reviewed emergency department medical records obtained from three university hospitals between July 2014 and December 2014. The proportion of adverse drug events among total emergency department visits was calculated. The cause, severity, preventability, and causative drug(s) of each adverse drug event were analyzed and compared between age groups (children/adolescents [<18 years], adults [18-64 years], and the elderly [≥65 years]). Of 59,428 emergency department visits, 2,104 (3.5%) were adverse drug event-related. Adverse drug event-related emergency department visits were more likely to be female and older. Multivariate logistic regression analysis revealed that compared to non- adverse drug event-related cases, adverse drug event-related emergency department visitors were more likely to be female (60.6% vs. 53.6%, p<0.001, OR 1.285, 95% CI 1.025-1.603) and older (50.8 ± 24.6 years vs. 37.7 ± 24.4 years, p<0.001, OR 1.892, 95% CI: 1.397-2.297). Comorbidities such as diabetes, chronic kidney disease, chronic liver disease, and malignancies were also significantly associated with adverse drug event-related emergency department visits. Side effects were the most common type of adverse drug events across age groups, although main types differed substantially depending on age. Serious adverse drug events, hospitalizations, and adverse drug event-related deaths occurred more frequently in the elderly than in adults or children/adolescents. The proportion of adverse drug event-related emergency department visits that were preventable was 15.3%. Causative drugs of adverse drug events varied considerably depending on age group. Adverse drug event features differ substantially according to age group. The findings suggest that an age-specific approach should be adopted in the preventive strategies to reduce adverse drug events.